Isolation, identification and molecular characterization of pathogenic organisms obtained from meat samples (cooked, semicooked and raw) of different areas of Dhaka city - Rudhy, Rabeya Tafsire (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Biotechnology, 2017.